The effect of alternative feeding strategies for broiler breeder pullets: 2. Welfare and performance during lay - Arrazola, A (Poult Sci, 2019)
Feeding broiler breeders to satiety has negative consequences on their health and reproduction. Alternative feeding strategies during rearing can improve welfare, although their implications during lay are not well understood. The objective was to examine the effect of rearing feeding treatments on the reproductive performance and feeding behavior of broiler breeders under simulated commercial conditions. At 3 wk of age, 1,680 Ross 308 pullets were allocated to 24 pens under 1 of 4 isocaloric treatments: 1) daily control diet; 2) daily alternative diet (40% soybean hulls and 1 to 5% calcium propionate); 3) 4/3 control diet (4 on-feed days, 3 non-consecutive off-feed days per week); and 4) graduated control diet. Feeding frequency of the graduated treatment varied with age and finished on a daily basis. At 23 wk of age, group sizes were adjusted to 40 hens, and 5 mature Yield Plus Males roosters were introduced to each pen. Pens were under the same daily feeding management and same diet during lay. The performance of broiler breeders (growth rate, body weight uniformity, and reproductive performance) was determined until 64 wk of age. At the end of lay, feeding motivation was examined with a feed intake test and a compensatory feeding test. Data were analyzed using linear mixed regression models, with pen nested in the models and age as a repeated measure. The laying rate of hens reared on the graduated treatment decreased slower compared to control hens, resulting in a higher cumulative egg production (178.2 ± 3.8 eggs/hen) than control hens (165.2 ± 3.8 eggs/hen, P < 0.01) by 64 wk of age. Hens reared on non-daily feeding treatments laid lighter eggs with relatively heavier yolks and had higher feed intake at the end of lay than hens fed daily during rearing (P = 0.02). In conclusion, rearing feeding treatments impacted the growth rate and body weight uniformity during lay, feeding motivation at the end of lay, and the laying rate and hatchability depending on hens’ age.